Price level targeting in a small open economy with financial frictions: Welfare analysis - Ali Dib; Caterina Mendicino; Yahong Zhang (Bank of Canada, 2008)
How important are the benefits of low price-level uncertainty? This paper explores the desirability of price-level path targeting in an estimated DSGE model fit to Canadian data. The policy implications are based on social welfare evaluations. Compared to the historical inflation targeting rule, an optimal price level targeting regime substantially reduces the welfare cost of business cycle fluctuations in terms of steady state consumption. The optimal price-level targeting rule performs also better than the optimal inflation targeting rule in minimizing the distortion generated by the presence of nominal debt contracts. The occurrence of financial shocks, which are among the main sources of business cycle fluctuations in the model, significantly contributes to quantify the welfare gains of price level targeting.
Keywords: E31; E32; E52; 330; Financial stability; Inflation and prices; Monetary policy framework; Inflation Targeting; Geldpolitisches Ziel; Preisniveau; Konjunktur; Verschuldungsrestriktion; Wohlfahrtseffekt; Kanada